Incidence, risk factors, and longitudinal outcome of seizures in long‐term survivors of pediatric brain tumors. (31st August 2015) - Ullrich, Nicole J.; Pomeroy, Scott L.; Kapur, Kush; Manley, Peter E.; Goumnerova, Liliana C.; Loddenkemper, Tobias
Summary Objective Seizures are common during and after treatment for a primary brain tumor. Our objective was to describe the incidence and risk factors for seizures in long‐term survivors of pediatric brain tumors. Methods In a retrospective, longitudinal study, we reviewed all consecutive patients during a 12‐month period who were at least 2 years post initial diagnosis of a brain tumor. Data collection included age at diagnosis, length of follow‐up, extent of initial resection, tumor histology, and treatment modalities. For patients who had experienced seizures at any time, the timing and frequency of seizures, seizure semiology, electroencephalography results, and anticonvulsant use were recorded. Univariate analyses and logistic regression were performed to assess risk factors. Results The cohort included 298 patients (140 female). Average duration of follow‐up was 7.6 years. Initial surgical resection was gross‐total in 109 patients, and subtotal for 143. Twenty‐nine patients underwent biopsy alone and 17 had no surgical intervention. Tumor location included posterior fossa (104; 36%), midline (98; 34%), cortical (85; 29%), and other (11; 3%). Most frequent diagnoses were low grade glioma, medulloblastoma, and ependymoma. Other treatments included cranial irradiation (N = 163) and chemotherapy (n = 127). Tumor recurrence occurred in 92 patients (30%). Seventy‐one patients had seizures (24%). Ongoing seizures at the time of most recent follow‐up were present in 42 patients. Risk factors for seizures included tumor location, tumor histology, tumor recurrence, and incomplete resection at time of initial presentation. Significance Seizures are a frequent comorbidity in pediatric brain tumor survivors, seen at presentation in 24% of patients and ongoing in 14%. Factors predisposing to seizures include tumor pathology (low/high grade glioma, glioneuronal tumor), cortical location, and subtotal resection. These data may assist in identification and management of patients at highest risk for seizures as well as identification of patients for potential treatment trials with antiepileptogenic agents.